2017
DOI: 10.1111/ced.13321
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CYP17 MSP AI (T-34C) and CYP19 codon 39 (Trp/Arg) polymorphisms with susceptibility to acne vulgaris

Abstract: The aim of this study was to detect the association of the cytochrome P450 (CYP) 17 T-34C and CYP19 T Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
0
11
0
6
Order By: Relevance
“…Some of the characteristics of the four studies included in the meta-analysis are shown in table 1. Two studies [8,13] were reported from Chinese, one [6] from Iranian, and one [14] from Polish populations. In all studies [6,8,13,14], the genotype distribution of the polymorphism in controls corresponded with Hardy-Weinberg equilibrium (HWE).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the characteristics of the four studies included in the meta-analysis are shown in table 1. Two studies [8,13] were reported from Chinese, one [6] from Iranian, and one [14] from Polish populations. In all studies [6,8,13,14], the genotype distribution of the polymorphism in controls corresponded with Hardy-Weinberg equilibrium (HWE).…”
Section: Resultsmentioning
confidence: 99%
“…In the overall analysis, there was heterogeneity in the allele, the heterozygote, and the dominant, models. There was no acne risk related to CYP17 (T-34C) in any of the genetic models in Caucasian ethnicity [6,14], whereas in Asian ethnicity [8,13] there was acne risk related to CYP17 (T-34C) without heterogeneity in analyses of C vs. T, CC vs. TT, CC + TC vs. TT, and CC vs. TT + TC in acne patients compared to the healthy controls; OR was 1.34 (95% CI: 1.05-1.72), 1.76 (95% CI: 1.08-2.87), 1.42 (95% CI: 0.95-2.11), and 1.52 (95% CI: 1.02-2.27), respectively.…”
Section: Analiza Statystycznamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in PCOS, where androgen is on a higher level, there will be IGFR activity present and, consequently, high CYP19 and dysfunctioning CYP17 levels are recorded [33,34]. In a study among 198 Iranian patients diagnosed with acne vulgaris conducted to shed some light on the association between acne vulgaris and two genotypes of CYP 450 (CYP 17 and CYP 19), it was proved that both genotypes are connected to the occurrence of acne vulgaris [35].…”
Section: Genetics Of Pcos and Its Dermatological Manifestationsmentioning
confidence: 99%